UPAYA PENINGKATAN KETERAMPILAN MENYIMAK PIDATO DAN CERAMAH DENGAN MENGGUNAKAN KATA KUNCI, SISWA KELAS IX A SMP NEGERI 14 KERINCI - Gusmarni Yelmita (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2017)
Learning achievement listening class IX students of SMPN 14 Kerinci still lacking. This is demonstrated by the average school had only reached 40%. Lack of learning outcomes is likely caused by several factors, among others: (1) the lack of learning techniques applied, (2) the absence of factors supporting the activities of listening, (3) lack of competence of teachers in implementing pembelajaranmenyimak, and (4) the lack of quality of the activities of listening to students , Hence the need for the study of learning to listen .. This classroom action research conducted with the aim of improving listening skills A speech class IX students of SMPN 14 Kerinci.Penelitian conducted three cycles. Implementation of the action taken is to apply keywords learning, (1) determine the major issues in the speech, (2) determine the content of the speech, (3) concluding message speech, (4) comment on the content of the speech with a logical reason and language was polite. Data collected by the analysis fortopolio student, teacher observation, student observation and questionnaires. The conclusion of this study is over the cycle I, II, III, can be summarized as follows: (1) the number of students who have the ability to determine the subject matter of speech increased (49.20% - 76.80%), (2) the number of students which has the ability to determine the content of the speech is increased (49.60% - 76.00%), (3) the number of students who have the ability to conclude the speech messages increased (50.68% - 74.80%), (4) the number of students has the ability commenting on the speech with a logical reason and language was polite increased (52.80% - 71.40%). The results of teacher observation and observation of students during learning activities taking place increases.